Music data analysis foundations and applications - Weihs, Claus; Jannach, Dietmar 1973-; Vatolkin, Igor 1980-; Rudolph, Günter (Series in computer science and data analysis, 2017)
"This textbook introduces the reader to the underlying mechanisms of automated music data analysis. Written by scientists working in different fields including physics, musicology, statistics, and computer science, it is the first self-contained book on this topic."--Page 4 of cover